2009
DOI: 10.1097/mou.0b013e32832ae176
|View full text |Cite
|
Sign up to set email alerts
|

Has botulinum toxin therapy come of age: what do we know, what do we need to know, and should we use it?

Abstract: Although still waiting for approval, BoNT/A detrusor injections can be safely offered to well informed patients with refractory neurogenic detrusor overactivity, as an alternative to more invasive therapies, such as bladder augmentation. Ongoing studies are expected to come up with the necessary information for definitive approval of BoNT/A in neurogenic detrusor overactivity patients. Regarding other possible applications such as idiopathic detrusor overactivity, benign prostatic enlargement and bladder pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…There is however still much to be learned about the optimal use as number of injections, dose, dilution and site of injections. 62,63 There is also need to determine the cause of the complications as generalized muscle weakness observed in several cases. 64,65 Further research should focus on these issues.…”
Section: Neurogenic Detrusor Over Activity: a Review Of The Efficacymentioning
confidence: 99%
“…There is however still much to be learned about the optimal use as number of injections, dose, dilution and site of injections. 62,63 There is also need to determine the cause of the complications as generalized muscle weakness observed in several cases. 64,65 Further research should focus on these issues.…”
Section: Neurogenic Detrusor Over Activity: a Review Of The Efficacymentioning
confidence: 99%
“…However, studies show no evidence for the development of tissue fibrosis with repeat botulinum injections. For example, repeated botulinum injections in the detrusor muscle of patients with neurogenic detrusor overactivity and neurogenic bladder dysfunction did not increase the risk of bladder fibrosis (9, 10). Furthermore, it has been reported that the use of botulinum can improve urethral wound healing in rat urethral muscle by reducing tensile muscle forces that can lead to scarring (11).…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum neurotoxin A is the most clinically relevant subtype. [ 31 ] It acts as a reversible inhibitor of neurotransmitter (mainly acetylcholine) release at the neuromuscular junction of both striated and smooth muscle. Indications include DSD, idiopathic and neurogenic detrusor overactivity (NDO).…”
Section: Methodsmentioning
confidence: 99%